An eco-evolutionary perspective on antimicrobial resistance in the context of One Health - Misshelle Bustamante; Siyu Mei; Ines M. Daras; G.S. van Doorn; Joana Falcao Salles; Marjon G.J. de Vos (iScience)
Summary: The One Health approach musters growing concerns about antimicrobial resistance due to the increased use of antibiotics in healthcare and agriculture, with all of its consequences for human, livestock, and environmental health. In this perspective, we explore the current knowledge on how interactions at different levels of biological organization, from genetic to ecological interactions, affect the evolution of antimicrobial resistance. We discuss their role in different contexts, from natural systems with weak selection, to human-influenced environments that impose a strong pressure toward antimicrobial resistance evolution. We emphasize the need for an eco-evolutionary approach within the One Health framework and highlight the importance of horizontal gene transfer and microbiome interactions for increased understanding of the emergence and spread of antimicrobial resistance.